Hydronephrosis as a symptom of clinically silent ureteral endometriosis - Lužný, Radim; Heřman, Hynek; Malchar, Ondřej; Pilka, Radovan (Ceska gynekologie, 2022)
OBJECTIVE: We present two case reports of asymptomatic ureteral endometriosis leading to hydronephrosis. We demonstrate the significance of routine ultrasound scanning of the upper urinary tract in patients with dia gnosed deep infiltrating endometriosis. CASE REPORTS: The first case report describes a symptomatic patient after a surgery for deep endometriosis. After the surgery, she was completely without symptoms, but during regular check-ups she developed progressive hydronephrosis on the right side and it did not respond to conservative treatment. Surgery deliberation of the ureter was indicated. The second case report describes a patient with already developed severe hydronephrosis on the left side. The functional kidney examination proved complete renal loss of the left kidney. Because of recurrent pyelonephritis in the nonfunctional kidney, nephrectomy was indicated. CONCLUSION: Ureteral endometriosis presents a rare, but insidious form of endometriosis, which is very often asymptomatic and diagnosed at a later stage. It can cause a complete silent loss of renal function. Routine ultrasound scanning examination of the upper urinary tract in all patients with diagnosed endometriosis could prevent this severe complication.
Keywords: hydronefróza; endometrióza; nemoci močovodu; ureteral endometriosis; Ultrasonography; ureter; Ureteral Diseases; ultrasonografie; ženské pohlaví; Humans; hydronephrosis; Female; Endometriosis; Ureter; routine US scanning; Hydronephrosis; lidé